2015
DOI: 10.4172/psychiatry.1000187
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function in Schizophrenia: A Review

Abstract: Schizophrenia is a mental disorder characterized by delusion, hallucination, formal thought disorder, disorganized or catatonic behavior, negative symptoms (e.g. emotional blunting, decreased initiative, impoverished speech etc.) and cognitive dysfunction. Though not described as diagnostic criteria, cognitive dysfunction is the strongest determinant of functional recovery as it has a gradual deteriorating effect on social and occupational functioning. It precedes coincides and outlasts positive symptoms. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Executive functions have been shown to be a robust predictor of lower adaptive behavior in ASD (Kenworthy et al, 2008;Matthews et al, 2015;Wallace et al, 2016) as well as in SSD (Bhattacharya, 2015;Fiksinski et al, 2019;Marinopoulou et al, 2016). Therefore, we anticipated that higher scores in the DEX-Sp (i.e., greater impairment) would predict lower scores in the VABS-II DLS Domain (i.e., greater problems in adaptive behaviors).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Executive functions have been shown to be a robust predictor of lower adaptive behavior in ASD (Kenworthy et al, 2008;Matthews et al, 2015;Wallace et al, 2016) as well as in SSD (Bhattacharya, 2015;Fiksinski et al, 2019;Marinopoulou et al, 2016). Therefore, we anticipated that higher scores in the DEX-Sp (i.e., greater impairment) would predict lower scores in the VABS-II DLS Domain (i.e., greater problems in adaptive behaviors).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review by Bhattacharya (2015) into EF in SSD found that monitoring, working memory, planning, switching and inhibitory control were among the most frequently affected EFs. Also, mental flexibility and the ability for abstraction have been linked to EF impairments in this disorder (Clark et al, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Future longitudinal studies, or even cross-sectional studies with different age groups, could help us to ascertain the developmental trajectory of EFs in ASD and closely study the dynamic changes that seem to be occurring in EFs in this clinical group . On the other hand, the progression of cognitive trajectory in SSD is different to the one observed in ASD as there seems to be a decline, rather than an improvement in cognitive performance [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%